Rheological characterization of starch gels: A biomass based sorbent for removal of polycyclic aromatic hydrocarbons (PAHs) - ABDURRAHMANOĞLU, SUZAN (ELSEVIER, 2019)
Environmental awareness increased the demand for the biomass based materials with superior properties instead of petroleum products. This study aims to prepare starch networks as sorbents for the removal of polycyclic aromatic hydrocarbons (PAHs). Two types of crosslinker, epichlorohydrine (ECH) and glutaraldehyde (GA), were choosed for the preparation of Gel-E and Gel-G networks, respectively. Rheological, swelling and morphological properties of the resulted materials were investigated as a function of various reaction parameters as starch, crosslinker and base concentration and also reaction temperature. The rheological measurements showed that while network formation of Gel-E hydrogels was strongly affected by the NaOH and starch concentration, the strength of the Gel-G hydrogels mainly depends on the crosslinker amount. Starch networks showed high PAH sorption capacities up to 1.42 g per gram sorbent with three model PAH molecules. Although PAH sorption capacities of the Gel-E networks are higher than those of Gel-G gels due to the pore sizes differences of the gel samples, both of them are promising materials as biosorbent for the PAH sorption applications due to the relatively high sorption capacities, low cost and simple preparation methods.
Keywords: Starch; Epichlorohydrin; Glutaraldehyde; Rheology; Polycyclic aromatic hydrocarbon